Meiotic recombination and chromosome segregation in Drosophila females. - McKim, K.S.; Jang, J.K.; Manheim, E.A. (Annual Review of Genetics, 2002)
In this review, we describe the pathway for generating meiotic crossovers in Drosophila melanogaster females and how these events ensure the segregation of homologous chromosomes. As appears to be common to meiosis in most organisms, recombination is initiated with a double-strand break (DSB). The interesting differences between organisms appear to be associated with what chromosomal events are required for DSBs to form. In Drosophila females, the synaptonemal complex is required for most DSB formation. The repair of these breaks requires several DSB repair genes, some of which are meiosis-specific, and defects at this stage can have effects downstream on oocyte development. This has been suggested to result from a checkpoint-like signaling between the oocyte nucleus and gene products regulating oogenesis. Crossovers result from genetically controlled modifications to the DSB repair pathway. Finally, segregation of chromosomes joined by a chiasma requires a bipolar spindle. At least two kinesin motor proteins are required for the assembly of this bipolar spindle, and while the meiotic spindle lacks traditional centrosomes, some centrosome components are found at the spindle poles.